21st Critical Management Skills to Counterfeit Resistance to Change: Springboard to Organizational Modification - Jaim, Irish Hazel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the adoption of 21st critical management skills among school administrators in overcoming resistance to change as a foundation for organizational modification at Zamboanga del Sur National High School. Anchored on the relationship between management skills, resistance to change, and organizational modification, the study focused on four dimensions: overcoming opposition, effectively engaging employees, implementing change in several stages, and communicating change effectively. The study employed a descriptive survey research design involving school administrators and teachers who were purposively selected as respondents. Data were gathered using a questionnaire-checklist and analyzed through weighted mean, ranking, and t-test. The findings revealed that school administrators consistently adopted the four identified management skills in addressing resistance to change. Among the practices, overcoming opposition obtained the highest adoption level, followed by effectively engaging employees, implementing change in several stages, and communicating change effectively. The results further showed a significant difference between the responses of school administrators and teachers regarding the adoption of 21st critical management skills in managing resistance to change. The study concluded that effective application of critical management skills is necessary to encourage cooperation, minimize resistance, and support organizational success. It recommended strengthening these skills through seminar-workshops and team-building activities for school administrators. The study contributes to SDG 4 – Quality Education by supporting effective educational leadership and institutional improvement, and to SDG 16 – Peace, Justice, and Strong Institutions by promoting participatory, transparent, and responsive organizational practices. The sustainability impact of the study lies in strengthening institutional sustainability through improved change management, collaboration, and governance practices within educational organizations.